SISTEM PRODUKSI KELAPA SAWIT DAN KARET DENGAN MEMBANDINGKAN HASIL PRODUKSI MENGGUNAKAN SIMULASI (STUDI KASUS: KABUPATEN KUANTAN SINGINGI) - Ira Puspita Sari; Robi Wahyu (LPPM Universitas Abdurrab, 2019)
Increased production of agricultural products is needed to maintain and improve the farm household's economy. Along with the increasing diversity of types of agriculture, especially agricultural oil palm and rubber crops. The diversity of farmers' ways to increase agricultural income by planting oil palm and rubber leaves farmers unfocused on one type of crop to be planted, some even switching from rubber to palm oil crops or vice versa. With the increase and utilization of the produce many farmers are hesitant to plant their land with oil palm or with rubber. To overcome the doubts in the community there needs to be a model with simulated results obtained with area, planting time, the same capital and produce different results. The expected result is to determine the ratio of production between oil palm and rubber.